(untitled) (Bioresearch Communications, 2022)
Urinary tract infections are a major public health concern. The formation of biofilm is the prime cause of antibiotic resistance by uropathogens. This study was conducted for the determination and biochemical characterization of uropathogens with drug resistance and biofilm formation capacity among Urinary Tract infected patients in Chattogram, Bangladesh. The samples (n=109) had been collected from the patients of Chattogram Medical College and Meghna diagnostic center, Chattogram, Bangladesh. Pathogens were biochemically identified from 109 urine samples, and their antibiotic susceptibility was determined using a disk diffusion test. Biofilm formation capacity was observed and confirmed using the Congo red agar (CRA) method and sequence analysis of the esp and cup A genes. Among 109 urine samples, 50 (45.87%) patients were tested positive in culture with gram-negative bacteria, where the most predominant genus was Escherichia coli (54%), Klebsiella spp. (30%) and Pseudomonas spp. (16%), which also showed sensitivity against the antibiotic Imipenem and Netilmicin. Besides, almost 82% of isolates showed resistance to Ampicillin. An epidemiological study showed that females (60%) are more susceptible to UTI compared to children and males; where it also showed that the people (68%) of greater Chattogram in summer are mostly infected with uropathogens along with diabetes (32%). In the biofilm formation test, it was found that 36% of uropathogens were exopolysaccharide producers. But no isolate was detected in PCR analysis. The present study showed that Imipenem can be used as a suitable antibiotic to treat UTI. Bioresearch Commu. 8(2): 1106-1112, 2022 (July)